Experimental study of diffusion of vaporized solvent in bitumen at elevated temperatures. (15th November 2020) - Meng, Lin; Kordestany, Amin; Maini, Brij; Dong, Mingzhe
Highlights: Design of a simple experimental rig for measurements of solvent diffusivity in liquids at high temperatures. New experimental data on diffusivity of hydrocarbon solvents in bitumen at high temperatures. A new correlation for predicting solvent diffusivity in bitumen. Abstract: The diffusion coefficient of gaseous solvent in bitumen is an essential parameter in numerical modeling of solvent-assisted thermal recovery processes. The reported measurements of solvent diffusion coefficient are relatively scarce, especially at the high temperature. In this study, a new constant-pressure experimental technique for one-dimensional diffusion tests, which accounts for the bitumen swelling and density change, was developed. A novel analytical model was used to interpret the experimental swelling data. The diffusion coefficients of propane, butane, pentane, hexane and heptane, were measured at temperatures varying from 90 °C to 195 °C. It was found that the diffusion coefficient, at similar solvent solubility, increases with the temperature for all solvents. For different solvents at the same temperature and solubility, the diffusion coefficient decreases with increasing molecular weight of the solvent. A modified power-law correlation of diffusion coefficient with bitumen viscosity and solvent-bitumen mixture viscosity was developed based on the experimental results from this study and other reported studies. The correlation can provide a quick estimation of the diffusion coefficient of gaseous solvent into bitumen.